The Vicious Circle of Corrosive Capital, Authoritarian Tendencies and State Capture in the Western Balkans - Prelec, Tena (Journal of Regional Security, 2020)
The presence of ‘non-Western actors’ in the Western Balkans has recently attracted the attention of policy-makers and academics alike, with the rise in prominence of non-EU countries coinciding with the weakening power of accession conditionality. While this trend was initially discussed in the context of a ‘new Cold War’ narrative, evidence-based research soon showed that this engagement is underpinned by particularistic interests at the top and ‘corrosive capital’. The governance dimension is therefore essential in understanding the ties existing between the Balkan countries and the non-Western actors. Making use of primary and secondary data, this article compares the modus operandi of two non-EU actors in the region: Russia and the United Arab Emirates. It is argued that non-transparent business deals can stimulate a normative shift in the Western Balkans’ political leadership away from pursuing the rule of law, and towards an authoritarian turn, while strengthening small circles of self-serving elites, at the expense of the citizenry at large. This is conceptualised as a ‘vicious circle’ of illiberalism and state capture, as viewed through the lens of corrosive capital.